Application of minority stress and the interpersonal theory of suicide in bisexual+ versus gay/lesbian young adults. Issue 4 (29th March 2022) - Chang, Cindy J.; Feinstein, Brian A.; Chu, Brian C.; Selby, Edward A.
Abstract: Introduction: Sexual minority young adults are at increased risk for suicidal ideation (SI) compared with heterosexual young adults. Though several frameworks exist to explain the development of suicide risk, including the Interpersonal Theory of Suicide (IPTS) and the Minority Stress Model, few studies have examined these frameworks simultaneously. This study examines these frameworks longitudinally among sexual minority young adults. Methods: A total of 792 sexual minority young adults (50% bisexual+, 50% gay/lesbian) completed an online survey at baseline, one‐month follow‐up, and two‐month follow‐up assessing constructs related to IPTS, the minority stress model, and SI. Results: Over half of our sample (52.9%) reported any SI at baseline. In the full sample, all types of minority stress at baseline were significantly associated with SI at two‐month follow‐up via perceived burdensomeness (PB) and thwarted belongingness (TB) at one‐month follow‐up. In the bisexual+ subsample, all bisexual‐specific minority stressors at baseline were significantly associated with SI at two‐month follow‐up via PB at one‐month follow‐up; internalized binegativity was also associated with SI via TB. However, effects became non‐significant when controlling for previous levels of the mediators and outcome variables. Conclusion: Both minority stress and IPTS are relevant for understanding suicide risk among sexual minority young adults.